PENGARUH LATIHAN SMALL SIDED GAMES TERHADAP KETERAMPILAN PASSING PADA TIM SEKOLAH SEPAK BOLA WONER 2012 KELOMPOK USIA (KU) 15 TAHUN - Dwitendi, Wahyu; Zainur, Zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is that the players from the Woner 2012 soccerschool team in the 15 yearage group (KU) often fail to provide good feedback to theirfriends in every practice or match. The purpose of this study was to determine the effect ofsmall sided games training on the passing skills of the Woner 2012 soccer school team inthe 15 year old (ku) age group. The method used in this research is the experimentalmethod. The research design carried out in this study was